The Equal Division of Inheritance among Sons and Daughters in Lê Society in Vietnam: A Revisit - Insun Yu (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
It has been generally accepted that in Lê society in Vietnam, when the parents died without a testament, their properties were divided equally among sons and daughters. Article 388 of the Lê Code is the basis for this interpretation. According to that article, if both parents died intestate, all children divided the property equally. However, Nhung Tuyet Tran has challenged this opinion recently, saying that daughters were discriminated against. According to her, article 388 only mentions the division among the sons and daughters, not necessarily an equal division. Second, the Hồng Ɖức Thiện Chính Thư of the first half of the sixteenth century states that the eldest son’s portion must be equal to that of the other sons (chúng tư, 衆子). Tran says that ‘chúng tư’ only means ‘sons’. Third, another regulation mentions equal division among brothers (huynh đệ, 兄弟). Fourth, in the testament of Vũ Vǎn Bȃn and his wife, dated July 1747, the daughter’s portion was much smaller than that of the brothers. In Tran’s opinion, the question is whether ‘chúng tu’ only means sons. A preeminent Japanese legal scholar conjectures that ‘tu’ (son) means ‘sons and daughters’ in the Tang and Song codes. Thus ‘chúng tư’ in Vietnamese law also must mean ‘sons and daughters.’ Therefore in the Hồng Ɖức Thiện Chính Thư, ‘huynh đệ’ must be interpreted as sons and daughters. Finally, Vũ Vǎn Bȃn and his wife in their testament state the equal division among the ‘chúng tư’ as applying to all children. But they do not explain the daughter’s lesser portion. I suggest that she could have received a dowry in compensation. All things considered, properties were likely divided equally among all children in Lê society. It follows that the daughters were never discriminated against. Received 10th October 2019; Revised 17th October 2019; Accepted 18th October 2019